Laboratory Investigation of the Effect of Three Decontamination Methods on Surface Alterations of Dental Implants - Khalilzadeh, Shohreh; Etesami, Soroush (Galen Medical Journal, 2025)
Background: The present study aimed to evaluate the effectiveness of three decontamination methods on the surface alterations of dental implants and the removal of bacterial plaque from their surfaces. Materials and Methods: In this experimental in vitro study, 24 titanium cylinders with sandblasted, large-grit, acid-etched (SLA) surfaces were contaminated with Staphylococcus aureus to simulate biofilm formation. Samples were randomly assigned to four groups (n = 6): titanium curette, diode laser, titanium brush, and saline flush control. Surface roughness (Ra and Rz) was measured using scanning electron microscopy (SEM) before and after cleaning. Colony-forming units (CFUs) were quantified post-treatment to assess bacterial removal. Statistical analyses included Kruskal-Wallis tests, Mann-Whitney pairwise comparisons, and one-way ANOVA with post hoc LSD tests (α = 0.05). Results: Surface roughness differed significantly among groups after cleaning (Ra, p = .002; Rz, p = .002). Titanium curette and titanium brush produced smoother surfaces than diode laser and control, with the curette achieving the greatest reduction in roughness. CFU analysis revealed significant differences among groups (F = 3.26, p = .043). Contrary to expectations, the saline flush control showed the lowest CFU counts, whereas titanium curette and titanium brush exhibited higher bacterial counts than control (p < .05), and diode laser did not differ significantly from control (p = .151). Conclusion: The titanium curette and titanium brush caused the samples' most significant surface roughness changes. However, the effectiveness of these methods for bacterial plaque removal was lower than that of the control group and the Diode laser group.